2013
DOI: 10.1186/2228-5326-3-57
|View full text |Cite
|
Sign up to set email alerts
|

Structural, morphological and optical properties of sol gel processed CdZnO nanostructured films: effect of precursor solvents

Abstract: Cadmium-doped zinc oxide (CZO) has been the potential candidate for the fabrication of low-cost transparent conductors having applications in energy conversion devices such as thin-film solar cells and light-emitting diodes. In this work, the effect of different precursor solvents on the structural, morphological, and optical properties of sol-gel spin-coated CZO films was investigated. The X-ray diffraction study has revealed the hexagonal wurtzite crystal structure with crystallite size ranging from 45 to 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…On the other hand, ZnO has a superior advantage in nanotechnology as it is easy to synthesize as nanostructures [1,2]. During the last decade, many reports have been published on the synthesis of ZnO nanoparticles [3], nanoflakes [4], hexagonal prismatic rods [5], nanoflowers [6], nanorods [7], nanopillars, or nanosheets using multiple methods of synthesis [8]. These studies have shown that the morphology of ZnO also plays a very important role in determining the physical properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ZnO has a superior advantage in nanotechnology as it is easy to synthesize as nanostructures [1,2]. During the last decade, many reports have been published on the synthesis of ZnO nanoparticles [3], nanoflakes [4], hexagonal prismatic rods [5], nanoflowers [6], nanorods [7], nanopillars, or nanosheets using multiple methods of synthesis [8]. These studies have shown that the morphology of ZnO also plays a very important role in determining the physical properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for a decrease in lattice parameter could be related to the decomposition of Zn 2 SnO 4 phase into the grains of ZnSnO 3 phase formed at high annealing temperature. Also, the crystallite size is calculated using the Debye-Scherrer formula [22,27]:…”
Section: Resultsmentioning
confidence: 99%
“…The precursor solvent such as methanol, ethanol, isopropanol and ethoxyethanol have found to greatly influence the structure property relationship for sol gel deposited films [21][22][23]. The use of different solvents has influence on the transmittance and average grain size of the sol gel coated metal oxide films [21,22]. The use of different solvents viz.…”
Section: Introductionmentioning
confidence: 99%
“…It has been attracted strong schooling effort for single optical and electrical features, and considerable applications in ultraviolet light emitters, transparent electronics, piezoelectric devices, gas sensors, spin electronics, solar cell and thin film transistors [3]. ZnO is commercially obtainable with feature like as relatively soft setback ZnOis not poisonous nature, environment-amicable, rise resistance to radiation harm, and rise thermal and chemical stabilization [4,5,6]. Using (PLD) technique become making of risefineness ZnO films at minimum heat than different ways , because the ablated particles were rise with laser-produced plume of plasma [6,7].…”
Section: Introductionmentioning
confidence: 99%